Pemanfaatan Limbah Kulit Kakao Menjadi Briket Arang Sebagai Bahan Bakar Alternatif (Kemandirian Energi) Pada Kelompok Masyarakat Dusun Beru-Beru, Desa Ongko, Kec Campalagian, Kab Polewali Mandar - Wahid, Masyitha; Nurdin, Gaby Maulida; Amaliah, Nur (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
Beru-Beru is one of the hamlets located in a mountainous area in Ongko Village, Campalagian, Polewali Mandar, West Sulawesi. In this hamlet, most of the residents work as cocoa farmers. However, the cocoa pod husk cannot be utilized optimally and ussually are abandoned as waste in the plantation area and produces an unpleasant odor. The method of this community service activities were through training and mentoring. The activity were attended by 20 participants from the villagers, 5 village officials, and students of the Program Studi Pendidikan Biologi of Universitas Sulawesi Barat. The training activities were carried out by involving community groups including youth organizations, housewives and several Ongko Village officials as the partners. The purpose of this activity was to provide material counseling related to the utilization of cocoa pod husk into charcoal briquettes and its processing. The whole activity was remarkable, which was indicated by the interest and enthusiasm of the attandee in participating in the entire series of activities, especially when practicing the making of charcoal briquette. These products can provide additional value to local commodities because they were made from cocoa pod husks which are considered as wastes and cocoa as one of the largest agricultural commodities at Beru-Beru, Ongko Village. Cocoa briquettes can be used as an alternative energy source or renewable fuel.